Analisis Perbedaan Abnormal Return dan Trading Volume Activity Pada Sekitar Cum Dividend Date - Tias Marganing Sih; Tatang Ary Gumanti; Hadi Paramu (e-Journal Ekonomi Bisnis dan Akuntansi, 2019)
The purpose of this research is to analyze the difference of Abnormal Return and Trading Volume Activity in each sector of shares around cum dividend date. The population in this study are all companies listed on the Indonesia Stock Exchange (IDX), the sampling is done by purpusive sampling method and obtained 156 samples. The method of analysis used in this study is by Kruskal-Wallis test. The results showed that there was no difference of Abnormal Return on stock sectors on cum dividend date. This research also shows that there is no difference of Trading Volume Activity before before cum dividend date, ex-dividend date and after ex-dividend date. It shows that the cum dividend date event has not become a consideration for investors to invest. Keywords: Abnormal Return, Cum Dividend Date, Dividend, Trading Volume Activity.